Influence of hydrolysis on electrospinnability of chitosan/polyvinyl alcohol blends solution and fiber diameter distribution - Umma Habiba; Amalina M. Afifi; Bee, Chin Ang; Sepehr Talebian (Universiti Kebangsaan Malaysia, 2016)
In this study, the effect of hydrolysis on electrospinnability of chitosan/PVA blend solution has been investigated. Since crude chitosan (Mw=8.96105 g/mole, DD=40%) could not be dissolved even in concentrated acetic acid, it was hydrolyzed with 33.5 wt. % of NaOH at 90°C for 24 and 42 h. Hydrolyzed chitosan with two different time duration was analyzed using Fourier transform infrared (FTIR). Morphology of the product nanofiber was investigated by field emission scanning electron microscope (FESEM.). FTIR results showed that the hydrolysis did not destroy the molecular backbone of chitosan but increased the degree of deacetylation from 40 to 84% and 92% for 24 and 42 h hydrolysis time, respectively. FESEM image analysis was carried out and histogram was drawn to study on the distribution of fiber diameter. It showed that though the composition of chitosan/PVA remained the same, but mean fiber diameter, standard deviation and required applied voltage for electrospinning was smaller for the solution containing maximum time hydrolyzed chitosan. It indicated that longer hydrolysis time resulted in finer nanofiber which mostly attributed to lower required voltage for electrospinning. Threshold composition for defect free fiber is 50:50 and 60:40 of chitosan/PVA for 24 and 42 h hydrolysis, respectively. It meant that 42 h hydrolysis ensured the presence of more chitosan in the chitosan/PVA polymer blend because of smaller presence of amino group in chitosan molecule.